Performance of plastic waste in asphalt mixture through dry process - Saiful Amri, Muhammad Ghafi (2019)
Plastic have become part of our today’s lifestyle. It is used for any needs of our daily life such as packaging, for protecting purpose, and serving purpose. The mass production of plastic would be good as its can produce a high incomes for the industries. There are some contradict in plastic industries which it can be a waste material and give the bad effect in environment. The disposal of waste plastic seems to be a major problem worldwide since the production of it may be high due to the high demand. Plastic is a non-biodegradable and it mainly consists of low-density polytethylene. Furthermore, it is logically to be mixed into the bituminous mixes for road construction rather than burning the waste plastic that can lead to the bad environmental pollution. The researched of the waste plastic added into the asphalt mixture had been carried on to to investigate the performance of waste plastic between modified asphalt mixture and conventional asphalt mixture and to study the optimum percentage of plastic waste added in asphalt mixture. This study used several test to identify the performance of the waste plastic in the asphalt mixture. Marshall test, resilient modulus test and dynamic creep test had been done by taking three samples of each percentage of plastic which is 0%, 5%, 7% and 9%. For the Resilient Modulus test, at 25°C the conventional asphalt mixture show the best result compared to the modified asphalt mixture at any percentage of waste plastic added. 7% of plastic added is the highest result before it decreased when 9% of waste plastic is added. At 40°C the result quite not constant which it increased and decreasing at every stage of percentages. For the dynamic creep test, the optimum asphalt mixture is at 9% where it shows greater result compare to the other percentage of the waste plastic added. This shows that the performance of the waste plastic in modified asphalt mixture influence the result of every test that had been done. The optimum modified asphalt mixture is different at every test conducted. It can be concluded that the percentage of plastic added may give the greater result compare to the conventional asphalt mixture.